1998
DOI: 10.1074/jbc.273.15.9031
|View full text |Cite
|
Sign up to set email alerts
|

A Chimeric Protein C Containing the Prothrombin Gla Domain Exhibits Increased Anticoagulant Activity and Altered Phospholipid Specificity

Abstract: To determine the structural basis of phosphatidylethanolamine (PE)-dependent activated protein C (APC) activity, we prepared a chimeric molecule in which the Gla domain and hydrophobic stack of protein C were replaced with the corresponding region of prothrombin. APC inactivation of factor Va was enhanced 10 -20-fold by PE. Protein S enhanced inactivation 2-fold and independently of PE. PE and protein S had little effect on the activity of the chimera. Factor Va inactivation by APC was approximately 5-fold les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
75
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(88 citation statements)
references
References 68 publications
13
75
0
Order By: Relevance
“…It has been shown that replacing the protein C Gla domain with that of prothrombin in a protein C/prothrombin chimera 45 causes a translocation of the APC active site toward the phospholipid surface from 9.4 to 8.9 nm compared with wild-type APC. 46 As demonstrated for this chimera, it is possible that the prothrombin Gla domain of Gla FII -PS may similarly translocate PS toward the phospholipid surface, resulting in impaired alignment of the TSR and EGF1 domains with APC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that replacing the protein C Gla domain with that of prothrombin in a protein C/prothrombin chimera 45 causes a translocation of the APC active site toward the phospholipid surface from 9.4 to 8.9 nm compared with wild-type APC. 46 As demonstrated for this chimera, it is possible that the prothrombin Gla domain of Gla FII -PS may similarly translocate PS toward the phospholipid surface, resulting in impaired alignment of the TSR and EGF1 domains with APC.…”
Section: Discussionmentioning
confidence: 99%
“…on April 8, 2019. by guest www.bloodjournal.org From replaced by the prothrombin Gla domain has been found to be insensitive to PS in a plasma clotting assay 45 ; in addition, PS dependence is associated with the C-terminal part of the protein C Gla domain. 45 Thus, it was suggested that PS functions in plasma are mainly dependent on interaction with APC and that this interaction is disrupted by replacing the Gla domain of protein C with that of prothrombin. 45 Our findings suggest that replacing the PS Gla domain with the prothrombin Gla domain results in similar disruption of the PS-APC interaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was originally suggested that PT inhibited the APC cleavage by serving as a competitive inhibitor to protein S (34). However, more recent studies demonstrated inhibition of APC-mediated FVa inactivation also in the absence of protein S (35,36). The mechanism of the PT-dependent inhibition of APC and/or protein S is not known.…”
mentioning
confidence: 99%